Method for manufacturing copper particle, conductive paste, and substrate
By vibrating and multi-step processing of copper particles during the drying process, the problem of insufficient filling properties of copper particles is solved, and the filling rate and conductive properties of conductive clay and substrate are significantly improved.
Patent Information
- Application Number
- JP2023169399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The prior art is difficult to obtain copper particles to improve fillability, affecting the filling rate and conductivity of conductive clay and substrates.
By vibrating and drying the aqueous copper particles during the drying process, the moisture content is controlled to be 30% or less, and separation, surface treatment and multiple reduction steps are adopted during the production process to improve the degree of powderization of the copper particles.
It significantly improves the filling and conductivity of copper particles, simplifies the production process, and improves the yield and quality of copper particles.
Smart Images

Figure 2025059353000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing copper particles, a conductive paste, and a substrate. [Background technology]
[0002] As a technique relating to copper particles, for example, the technique described in Patent Document 1 can be mentioned.
[0003] Patent Document 1 describes copper powder produced by a wet method, which has an absolute value of a zeta potential of 20 mV or more. It is described that the copper powder in Patent Document 1 can obtain easily crushable copper powder in which residual secondary particles are sufficiently reduced while reducing the burden of the crushing and classification processes from the dried cake. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-50947 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a method for producing copper particles that can yield copper particles with improved packing properties, and a conductive paste and a substrate that use the copper particles. [Means for solving the problem]
[0006] According to the present invention, there are provided a method for producing copper particles, a conductive paste, and a substrate as described below.
[0007] [1] The method includes a step (A) of drying the hydrous copper particles while vibrating the particles, The method for producing copper particles, wherein the moisture content of the hydrated copper particles is 30% by mass or less when the entirety of the hydrated copper particles is taken as 100% by mass. [2] The method for producing copper particles described in [1] above, wherein the moisture content of the hydrated copper particles is 5% by mass or more when the entire hydrated copper particles are taken as 100% by mass. [3] The method for producing copper particles according to [1] or [2], wherein in the step (A), the hydrous copper particles are dried using a vibration dryer. [4] The method for producing copper particles according to any one of the above [1] to [3], wherein in the step (A), the drying temperature is 30° C. or higher and 100° C. or lower. [5] The method for producing copper particles according to any one of [1] to [4] above, wherein in the step (A), the drying time is from 10 minutes to 24 hours. [6] A step (B) of preparing a copper particle dispersion liquid (a); The method for producing copper particles according to any one of the above [1] to [5], further comprising a step (C) of subjecting the copper particle dispersion liquid (a) to solid-liquid separation to obtain the hydrous copper particles. [7] The method for producing copper particles described in [6] above, wherein in the step (C), the hydrated copper particles are obtained by at least one method selected from a centrifugation method and a filtration method. [8] The step (B) includes a step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant; The method for producing copper particles described in [6] or [7] above, further comprising a step (B-2) of reducing the divalent copper compound to obtain a copper particle dispersion liquid (a). [9] The method for producing copper particles described in [8] above, wherein in the step (B-1), the dispersant includes at least one selected from the group consisting of gelatin, casein, sodium caseinate, ammonium caseinate, starch, dextrin, agar, sodium alginate, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, sodium polyacrylate, ammonium polyacrylate, stearic acid, polyethylene glycol, citric acid, aniline, and aniline derivatives.
[10] The method for producing copper particles according to any one of [1] to [9] above, wherein the temperature at which the copper particles have a shrinkage of 1.0% calculated by the shrinkage measurement described below is 200° C. or higher. [Shrinkage rate measurement] 1 g of copper particles is weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the granule sample is press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate becomes 1.0% is calculated.
[11] The copper particles have a tap density of 2.5 g / cm as measured in accordance with JIS Z2512:2012. 3 The method for producing copper particles according to any one of the above [1] to
[10] .
[12] D calculated by the following particle size measurement 1 of the copper particles 50 The method for producing copper particles according to any one of the above [1] to
[11] , wherein the particle diameter (H2O) is 0.10 μm or more and 1.00 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively.
[13] D calculated by the following particle size measurement 1 of the copper particles 10 The method for producing copper particles according to any one of the above [1] to
[12] , wherein the particle diameter (H2O) is 0.05 μm or more and 0.50 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively.
[14] D calculated by the following particle size measurement 1 of the copper particles 95 The method for producing copper particles according to any one of the above [1] to
[13] , wherein the particle diameter (H2O) is 0.20 μm or more and 2.00 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively.
[15] D, calculated by the following particle size measurement 1 of the copper particles 95 Particle diameter (H2O) is D 10 The method for producing copper particles according to any one of the above [1] to
[14] , wherein the particle diameter divided by (H2O) is 4.20 or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively.
[16] The method for producing copper particles according to any one of [1] to
[15] above, wherein the copper particles have an oxygen content of 0.70 mass% or less as measured in accordance with JIS H1067:2002.
[17] The method for producing copper particles according to any one of [1] to
[16] above, wherein the copper particles have a carbon content of 1.50 mass% or less as calculated by the following carbon content measurement. [Carbon content measurement] Weigh out 0.5g of copper particles, add 1.5g of tungsten powder, 0.5g of iron powder, and 0.5g of tin powder as combustion improvers, and measure using a carbon / sulfur analyzer under the following conditions: in an oxygen stream, flow rate: 3L / min, combustion method: high-frequency heating, combustion time: 60 seconds, detection method: infrared absorption method, and calculate the carbon content.
[18] A conductive paste comprising copper particles obtained by the method for producing copper particles according to any one of [1] to
[17] above.
[19] A substrate comprising the conductive paste according to
[18] or a sintered body of the conductive paste.
[20] The substrate according to
[19] above, which is a low-temperature co-fired ceramic substrate. Effect of the Invention
[0008] According to the present invention, there can be provided a method for producing copper particles capable of obtaining copper particles with improved filling property, and a conductive paste and a substrate using the copper particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described. A numerical range "A to B" represents A or more and B or less, unless otherwise specified.
[0010] [Method of manufacturing copper particles] Copper particles are used, for example, as a conductive paste. In addition, the conductive paste containing copper particles is used, for example, as a wiring conductor of a substrate. When the conductive paste containing copper particles is used as a wiring conductor of a substrate, the conductive paste may be filled into a via hole of the substrate. Therefore, it is required to further improve the filling rate of copper particles in the via hole. The present invention provides a method for producing copper particles that can yield copper particles with improved packing properties, and a conductive paste and a substrate that use the copper particles.
[0011] The method for producing copper particles of this embodiment includes a step (A) of drying hydrous copper particles while vibrating them, and the moisture content of the hydrous copper particles is 30 mass% or less when the entire hydrous copper particles are taken as 100 mass%.
[0012] Furthermore, according to the method for producing copper particles of this embodiment, the proportion of powdery copper particles in the copper particles obtained after step (A) can be further increased. Here, powdery copper particles refer to copper particles that are in powder form without being subjected to a crushing treatment in a mortar, etc. If the ratio of powdery copper particles in the copper particles obtained after step (A) is increased, the manufacturing process can be further simplified and the yield of copper particles can be further improved.
[0013] It is preferable that the method for producing copper particles of this embodiment further includes a step (B) of preparing a copper particle dispersion liquid (a), and a step (C) of performing solid-liquid separation of the copper particle dispersion liquid (a) to obtain the hydrous copper particles.
[0014] In this embodiment, the hydrous copper particles refer to a copper particle cake containing moisture, and refer to copper particles in a state before drying after the copper particle dispersion liquid (a) is subjected to solid-liquid separation.
[0015] Each step of the method for producing copper particles of this embodiment will be described below.
[0016] <Step (A) of drying the hydrous copper particles while vibrating> The method for producing copper particles of this embodiment includes a step (A) of drying hydrous copper particles while vibrating them.
[0017] The moisture content of the hydrous copper particles is 30% by mass or less when the entire hydrous copper particles are taken as 100% by mass. The moisture content of the hydrous copper particles, when the entire hydrous copper particles are taken as 100% by mass, is, from the viewpoint of improving the packing property of the obtained copper particles and further increasing the proportion of powdery copper particles in the obtained copper particles, preferably 28% by mass or less, more preferably 25% by mass or less, even more preferably 23% by mass or less, and even more preferably 20% by mass or less, and the lower limit is not particularly limited, but may be, for example, 5% by mass or more, 7% by mass or more, or 10% by mass or more. The moisture content of the hydrous copper particles means the moisture content of the hydrous copper particles before drying.
[0018] In step (A), the drying temperature is preferably 30°C or higher, more preferably 40°C or higher, even more preferably 45°C or higher, even more preferably 50°C or higher, and even more preferably 60°C or higher, from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles, and is preferably 100°C or lower, more preferably 95°C or lower, even more preferably 90°C or lower, and even more preferably 80°C or lower, from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles.
[0019] In step (A), from the viewpoint of further increasing the proportion of powdery copper particles in the obtained copper particles, the drying time is preferably 10 minutes or more, more preferably 30 minutes or more, even more preferably 60 minutes or more, even more preferably 80 minutes or more, even more preferably 120 minutes or more, and even more preferably 150 minutes or more, and from the viewpoint of further improving productivity, the drying time is preferably 24 hours or less, more preferably 12 hours or less, even more preferably 5 hours or less, and even more preferably 4 hours or less.
[0020] Step (A) may be carried out under reduced pressure or normal pressure, but is preferably carried out under reduced pressure.
[0021] In step (A), the method for drying the hydrous copper particles while vibrating them is not particularly limited, but it is preferable to dry the hydrous copper particles using a vibration dryer, and it is more preferable to dry the hydrous copper particles using a vertical vibration dryer. As the vertical vibration dryer, for example, a small vibration dryer VU-15 type (manufactured by Chuo Kakoki Co., Ltd.) can be used.
[0022] <Step (B) of Preparing Copper Particle Dispersion Liquid (a)> The method for producing copper particles of this embodiment preferably further includes a step (B) of preparing a copper particle dispersion liquid (a).
[0023] The copper particle dispersion liquid (a) means a solution in which copper particles are dispersed in a solvent such as water. The solvent preferably contains water.
[0024] Step (B) preferably comprises a step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant, and a step (B-2) of reducing the divalent copper compound to obtain a copper particle dispersion liquid (a).
[0025] The step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant is carried out, for example, by adding a divalent copper compound to a solvent such as water, stirring the mixture, and then adding a dispersant.
[0026] The divalent copper compound includes, for example, at least one selected from the group consisting of copper sulfate, copper oxide, copper chloride, copper carbonate, copper nitrate, and the like, and preferably includes copper sulfate.
[0027] The dispersant is not particularly limited, but preferably includes at least one selected from the group consisting of gelatin, casein, sodium caseinate, ammonium caseinate, starch, dextrin, agar, sodium alginate, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, sodium polyacrylate, ammonium polyacrylate, stearic acid, polyethylene glycol, citric acid, aniline, and aniline derivatives, more preferably includes at least one selected from the group consisting of gelatin, casein, sodium caseinate, and ammonium caseinate, and even more preferably includes gelatin.
[0028] In step (B-1), the content of the dispersant, relative to 100 parts by mass of the copper compound, is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1.0 parts by mass or more, and is preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, from the viewpoint of further improving the dispersibility of the copper particles.
[0029] Step (B-2) of reducing a divalent copper compound to obtain a copper particle dispersion liquid (a) is carried out, for example, by adding a reducing agent to the dispersion liquid obtained in step (B-1) and reducing the divalent copper compound to obtain copper particles.
[0030] The reducing agent includes at least one selected from the group consisting of ascorbic acid; hydrazine-based reducing agents such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate; sodium borohydride; sodium sulfite; sodium hydrogensulfite; sodium thiosulfate; sodium nitrite; sodium hyponitrite; phosphorous acid; sodium phosphite; hypophosphorous acid; sodium hypophosphite; aldehydes; alcohols; amines; and sugars.
[0031] The step (B-2) may be carried out under heating conditions in order to further promote the reduction of the divalent copper compound. The heating temperature is not particularly limited, but may be, for example, 10° C. or higher, 20° C. or higher, and 90° C. or lower, or 80° C. or lower.
[0032] In the step (B-2), the reduction step may be carried out only once, or may be carried out multiple times, but it is preferable to carry out the reduction step multiple times. That is, the step (B-2) preferably comprises a first reduction step and a second reduction step.
[0033] In the first reduction step, the reducing agent preferably comprises ascorbic acid. In the second reduction step, the reducing agent preferably comprises a hydrazine-based reducing agent, more preferably comprises hydrazine.
[0034] The method may further include a step of adjusting the pH of the dispersion between the first reduction step and the second reduction step. The step of adjusting the pH of the dispersion liquid is, for example, a step of adjusting the pH to 9.0 or more and 14.0 or less. The step of adjusting the pH of the dispersion liquid is carried out, for example, by adding a pH adjuster such as an aqueous sodium hydroxide solution to the dispersion liquid.
[0035] The copper particle dispersion liquid (a) may be free of the dispersant. The removal of the dispersant is carried out, for example, by adding a remover to the copper particle dispersion liquid (a). As the remover, for example, an aqueous solution of a hydroxide salt such as an aqueous solution of sodium hydroxide or an aqueous solution of potassium hydroxide; ion-exchanged water; or the like can be used.
[0036] The copper particles in the copper particle dispersion liquid (a) may be surface-treated. The surface treatment is carried out by treating the surfaces of the copper particles with a surface treatment agent such as a saturated fatty acid salt, e.g., sodium stearate; or an unsaturated fatty acid salt, e.g., sodium oleate.
[0037] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The method for producing copper particles of this embodiment preferably further includes a step (C) of subjecting the copper particle dispersion liquid (a) to solid-liquid separation to obtain hydrous copper particles. Here, the copper particle dispersion liquid (a) in the step (C) includes a copper particle dispersion liquid (a) from which the dispersant has been removed, surface treatment has been performed, and the like.
[0038] The method for obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a) is not particularly limited. For example, the hydrous copper particles can be obtained by at least one method selected from the group consisting of centrifugation, filtration, decantation, and the like. Among these, from the viewpoint of adjusting the moisture content of the hydrous copper particles to an appropriate range, it is preferable to obtain the hydrous copper particles by at least one method selected from centrifugation and filtration.
[0039] <Other processes> The method for producing copper particles of this embodiment may include other steps as appropriate. As the other steps, for example, a crushing step and the like can be mentioned.
[0040] [Copper particles] Hereinafter, preferred embodiments of the copper particles obtained by the copper particle manufacturing method of this embodiment will be described.
[0041] D of the copper particles of this embodiment 10 The particle size (H2O) is preferably 0.05 μm or more, more preferably 0.10 μm or more, even more preferably 0.15 μm or more, even more preferably 0.20 μm or more, even more preferably 0.25 μm or more, and is preferably 0.50 μm or less, more preferably 0.45 μm or less, even more preferably 0.40 μm or less.
[0042] D of the copper particles of this embodiment 50The particle size (H2O) is preferably 0.10 μm or more, more preferably 0.20 μm or more, even more preferably 0.25 μm or more, even more preferably 0.30 μm or more, even more preferably 0.35 μm or more, even more preferably 0.40 μm or more, and is preferably 1.00 μm or less, more preferably 0.80 μm or less, even more preferably 0.70 μm or less, even more preferably 0.65 μm or less, even more preferably 0.60 μm or less.
[0043] D of the copper particles of this embodiment 95 The particle size (H2O) is preferably 0.20 μm or more, more preferably 0.30 μm or more, even more preferably 0.40 μm or more, and even more preferably 0.50 μm or more. From the viewpoint of further improving the filling property, it is preferably 2.00 μm or less, more preferably 1.80 μm or less, even more preferably 1.60 μm or less, and even more preferably 1.50 μm or less.
[0044] The copper particles of this embodiment, D 95 Particle diameter (H2O) is D 10 From the viewpoint of further improving the filling property, the value divided by the particle size (H2O) is preferably 4.20 or less, more preferably 4.10 or less, even more preferably 4.00 or less, even more preferably 3.90 or less, and even more preferably 3.80 or less, and the lower limit is not particularly limited, but may be, for example, 1.10 or more, 1.30 or more, 1.50 or more, or 1.80 or more.
[0045] The copper particles of this embodiment, D 95 Particle size (H2O) to D 10 From the viewpoint of further improving the filling property, the value obtained by subtracting the particle size (H2O) is preferably 1.50 μm or less, more preferably 1.40 μm or less, even more preferably 1.30 μm or less, even more preferably 1.20 μm or less, and even more preferably 1.10 μm or less, and the lower limit is not particularly limited, and may be, for example, 0.05 μm or more, 0.10 μm or more, 0.20 μm or more, or 0.25 μm or more.
[0046] Here, D 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 The particle size (H2O) refers to the value calculated by Particle Size Measurement 1.
[0047] [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 Obtain the particle size (H2O) values, respectively. In particle size measurement 1, the dispersant refers to polyoxyethylene (20) sorbitan monolaurate.
[0048] D of the copper particles of this embodiment 10 The particle size (img) is preferably 0.05 μm or more, more preferably 0.10 μm or more, and is preferably 0.50 μm or less, more preferably 0.40 μm or less.
[0049] D of the copper particles of this embodiment 50 The particle size (img) is preferably 0.10 μm or more, more preferably 0.20 μm or more, even more preferably 0.30 μm or more, and is preferably 1.00 μm or less, more preferably 0.80 μm or less, even more preferably 0.60 μm or less.
[0050] D of the copper particles of this embodiment 90 The particle size (img) is preferably 0.20 μm or more, more preferably 0.40 μm or more, even more preferably 0.50 μm or more, and preferably 2.00 μm or less, more preferably 1.80 μm or less, even more preferably 1.50 μm or less, even more preferably 1.20 μm or less.
[0051] Here, D 10 Particle size (img), D 50Particle size (img), and D 90 The particle size (img) refers to the value calculated by particle size measurement 2.
[0052] [Particle size measurement 2] The images obtained by scanning electron microscope were analyzed to determine the 10 Particle size (img), D 50 Particle size (img) and D 90 Obtain the particle size (img) value for each. More specifically, D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) refers to a value calculated by the method described in the Examples.
[0053] The copper particles of this embodiment, D 50 Particle diameter (H2O) is D 50 From the viewpoint of further improving the filling property, the value divided by the particle size (img) is preferably 1.50 or less, more preferably 1.45 or less, even more preferably 1.40 or less, and even more preferably 1.35 or less, and the lower limit is not particularly limited, but may be, for example, 0.50 or more, 0.60 or more, or 0.70 or more.
[0054] From the viewpoint of further improving filling ability, the oxygen content of the copper particles of this embodiment, measured in accordance with JIS H1067:2002, is preferably 0.70% by mass or less, preferably 0.68% by mass or less, more preferably 0.67% by mass or less, even more preferably 0.66% by mass or less, even more preferably 0.65% by mass or less, and even more preferably 0.63% by mass or less, and the lower limit is not particularly limited, but may be, for example, 0.01% by mass or more, 0.10% by mass or more, 0.20% by mass or more, 0.30% by mass or more, 0.40% by mass or more, or 0.45% by mass or more.
[0055] From the viewpoint of further suppressing a decrease in electrical conductivity, the carbon content of the copper particles of this embodiment is preferably 1.50 mass% or less, more preferably 1.00 mass% or less, even more preferably 0.80 mass% or less, even more preferably 0.75 mass% or less, even more preferably 0.70 mass% or less, even more preferably 0.65 mass% or less, even more preferably 0.62 mass% or less, and even more preferably 0.60 mass% or less, and the lower limit is not particularly limited, but may be, for example, 0.01 mass% or more, 0.10 mass% or more, 0.20 mass% or more, 0.30 mass% or more, or 0.40 mass% or more. Here, the carbon content refers to a value calculated by the carbon content measurement described below.
[0056] [Carbon content measurement] Weigh out 0.5g of copper particles, add 1.5g of tungsten powder, 0.5g of iron powder, and 0.5g of tin powder as combustion improvers, and measure using a carbon / sulfur analyzer under the following conditions: in an oxygen stream, flow rate: 3L / min, combustion method: high-frequency heating, combustion time: 60 seconds, detection method: infrared absorption method, and calculate the carbon content.
[0057] The copper particles of the present embodiment may contain other elements in addition to copper, oxygen, and carbon. Examples of the other elements include nitrogen, chlorine, boron, etc. The content of the other elements is not particularly limited and may be an appropriate amount.
[0058] The temperature at which the copper particles of this embodiment have a shrinkage rate of 1.0% is preferably 200°C or higher, more preferably 300°C or higher, even more preferably 400°C or higher, even more preferably 500°C or higher, even more preferably 600°C or higher, even more preferably 650°C or higher, and even more preferably 700°C or higher, and the upper limit is not particularly limited, but may be, for example, 1000°C or lower, 950°C or lower, or 900°C or lower. It is preferable that the temperature at which the shrinkage rate becomes 1.0% is equal to or higher than the above lower limit, because when a conductive paste containing copper particles is used for a low-temperature co-fired ceramic substrate, the wiring conductor and the ceramic substrate can be co-fired more efficiently. Here, the temperature at which the shrinkage rate is 1.0% means a value calculated by the following shrinkage rate measurement.
[0059] [Shrinkage rate measurement] 1 g of copper particles is weighed out and filled into a cylindrical mold with a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out and filled into a cylindrical mold with a diameter of 5 mm, and the granule sample is press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet with a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate becomes 1.0% is calculated.
[0060] The copper particles of this embodiment preferably have a tap density of 2.5 g / cm as measured in accordance with JIS Z2512:2012. 3 More preferably, 2.8 g / cm 3 More preferably, 3.0 g / cm 3 More preferably, 3.2 g / cm 3 More preferably, 3.5 g / cm 3 The upper limit is not particularly limited, but is, for example, 5.0 g / cm 3 or less, 4.8 g / cm 3 or less, 4.5 g / cm 3 or less, 4.3 g / cm 3 It may be the following:
[0061] [Uses of copper particles] The copper particles of the present embodiment can be used, for example, in conductive pastes, paints, inks, etc., and can be preferably used in conductive pastes.
[0062] [Conductive paste] The conductive paste of this embodiment contains copper particles obtained by the copper particle manufacturing method of this embodiment. The content of copper particles in the conductive paste of this embodiment, when the entire conductive paste is taken as 100 mass%, may be, for example, 1 mass% or more, 5 mass% or more, or 10 mass% or more, and may be 99 mass% or less, 97 mass% or less, or 94 mass% or less.
[0063] The conductive paste of the present embodiment may further contain a binder resin. The binder resin includes at least one selected from the group consisting of, for example, polyester resin, polyurethane resin, polyamide resin, polyvinyl chloride resin, polyacrylamide resin, polyether resin, acrylic resin, melamine resin, vinyl resin, phenol resin, epoxy resin, urea resin, vinyl acetate resin, polybutadiene resin, vinyl chloride-vinyl acetate copolymer resin, fluororesin, silicone resin, rosin, rosin ester, chlorinated polyolefin resin, modified chlorinated polyolefin resin, chlorinated polyurethane resin, cellulose-based resin, polyethylene glycol, polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyvinyl butyral, and polyvinylpyrrolidone.
[0064] The conductive paste of the present embodiment may further contain a solvent including at least one of water and an organic solvent. The organic solvent may be either a hydrophobic solvent or a hydrophilic solvent.
[0065] The hydrophobic solvent may be, for example, at least one selected from the group consisting of mineral oil, fatty acid, alcohol, and hydrocarbon.
[0066] Examples of the hydrophilic solvent include at least one selected from the group consisting of alkanediols such as ethylene glycol and propylene glycol; polyhydric alcohols such as glycerin; sugar alcohols; lower alcohols such as ethanol, methanol, propanol, and butanol; glycol ethers such as ethylene glycol monomethyl ether and ethylene glycol monoethyl ether; aliphatic amines such as methylamine and triethylamine; alkanolamines such as ethanolamine and triethanolamine; and amides such as N-methylacetamide and N-methylformamide.
[0067] The organic solvent may be used alone or in combination of two or more kinds.
[0068] The conductive paste of the present embodiment can be applied to a substrate by, for example, an inkjet method or a screen printing method, dried, and then heated to form a conductive member such as a copper particle-containing wiring or thin film.
[0069] The conductive paste of the present embodiment can be produced by a known method, for example, by mixing the above-mentioned materials using a mixer such as a three-roll mill, a bead mill, a ball mill, a planetary mixer, or a disperser.
[0070] [substrate] The substrate of this embodiment includes the conductive paste of this embodiment or a sintered body of the conductive paste of this embodiment. The substrate of the present embodiment includes, for example, a coating of the conductive paste of the present embodiment or a sintered body of the conductive paste of the present embodiment in a predetermined region of a base material.
[0071] The substrate of this embodiment is, for example, a low-temperature co-fired ceramic substrate, a printed circuit board, a flexible substrate, or the like, and is preferably a low-temperature co-fired ceramic substrate.
[0072] The substrate of this embodiment is used, for example, as an electronic substrate for an automobile, a substrate for a high frequency module, a substrate for a semiconductor package, and the like.
[0073] The substrate of the present embodiment can be manufactured by a known method. For example, the conductive paste of the present embodiment can be screen-printed on a predetermined region of a base material (e.g., a green sheet, etc.), a plurality of base materials on which the conductive paste is printed are stacked to produce a laminate, and the laminate is fired to manufacture the substrate.
[0074] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Furthermore, the present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES
[0075] The present embodiment will be described in detail below based on examples and comparative examples. Note that the present embodiment is not limited to the descriptions of these examples.
[0076] [Example 1] <Step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant> First, 670 g of copper sulfate (manufactured by JX Metals Corporation) was added as a divalent copper compound to 2.26 L of ion-exchanged water, and the mixture was stirred using a stirrer (manufactured by HEIDON, product name: BL300). A dispersant solution prepared by the method described below was then added to obtain a dispersion. (Method of preparing a dispersant solution) As a dispersant, 10.7 g of gelatin (derived from cow bone, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., weight average molecular weight 100,000 to 300,000) was added to 0.5 L of ion-exchanged water, and the mixture was stirred with a magnetic stirrer (manufactured by IKA Corporation, product name: C-MAG HS4 digital) to prepare a dispersant solution.
[0077] <Step (B-2) of Obtaining Copper Particle Dispersion Liquid (a) by Reducing Divalent Copper Compound> A reducing agent solution prepared by the method described below was added to the dispersion. The dispersion was heated to 40°C and stirred for 3 minutes to reduce the copper compound, and a copper compound dispersion (b) was obtained. Next, a 24% by mass aqueous solution of sodium hydroxide was added to the copper compound dispersion (b) under the condition of a solution temperature of 40°C until the pH of the solution reached 10.6. At this time, the adjustment time until the pH of the solution reached 10.6 was 30 minutes. 400 g of hydrazine (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added as a reducing agent to the copper compound dispersion (b) whose pH had been adjusted, and the solution was heated to 60°C and stirred for 60 minutes to reduce the copper compound, and a copper particle dispersion (a) was obtained. (Method of preparing reducing agent solution) As a reducing agent, 472 g of ascorbic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 2.0 L of ion-exchanged water, and the mixture was stirred with a magnetic stirrer (manufactured by IKA Corporation, product name: C-MAG HS4 digital) to prepare a reducing agent solution.
[0078] <Step of Removing Dispersant> After stopping the stirring of the copper particle dispersion (a) and removing the supernatant, 5050 g of 1.2 mass% sodium hydroxide aqueous solution was added as a remover to remove the dispersant, and the mixture was stirred for 10 minutes. After stopping the stirring again and removing the supernatant, a reducing agent aqueous solution prepared by adding 27 g of hydrazine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to ion-exchanged water was added to the copper particle dispersion (a), and the solution was heated to 50°C and stirred for 20 minutes. At this time, the pH of the copper particle dispersion (a) was 12.5.
[0079] <Surface treatment process> To the copper particle dispersion liquid (a) from which the dispersant had been removed, a surface treatment agent dispersion was prepared by adding 0.84 g of sodium stearate (manufactured by Kanto Chemical Co., Ltd.) to 0.5 L of ion-exchanged water as a surface treatment agent. The surface of the copper particles was then treated by adding the surface treatment agent dispersion to the copper particle dispersion liquid (a).
[0080] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was subjected to solid-liquid separation using a centrifuge (manufactured by Kokusan Co., Ltd., product name: H-36) at a rotation speed of 3500 rpm for 5 minutes to obtain hydrous copper particles. The water content of the obtained hydrous copper particles was 13% by mass when the entire hydrous copper particles were taken as 100% by mass.
[0081] <Step (A) of drying the hydrous copper particles while vibrating> 817 g of the hydrous copper particles were dried while vibrating using a vertical vibration dryer under reduced pressure conditions at a drying temperature of 50° C. for a drying time of 180 minutes to obtain copper particles. The vertical vibration dryer used here was a small vibration dryer VU-15 (manufactured by Chuo Kakoki Co., Ltd.) with an adapter attached to the vacuum filter section and the body length of the dryer extended. The weight of the obtained copper particles was 708 g. The proportion of powdery copper particles in the obtained copper particles was 59 mass %, and the proportion of lump copper particles was 41 mass %. Here, the powdery copper particles refer to copper particles that are in powder form without being subjected to a crushing treatment in a mortar or the like. The lump copper particles refer to copper particles other than powdery copper particles. The present inventors believe that the powdery copper particles are obtained by crushing the lump copper particles by vibration drying.
[0082] [Example 3] Hydrated copper particles were obtained in the same manner as in Example 1. The moisture content of the obtained hydrous copper particles is shown in Table 1.
[0083] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles charged, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain copper particles. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.
[0084] [Examples 2 and 4] The copper particles were subjected to surface treatment in the same manner as in Example 1 to obtain a copper particle dispersion liquid (a).
[0085] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was subjected to solid-liquid separation by suction filtration using qualitative filter paper (manufactured by ADVANTEC, product name: No. 131) to obtain hydrous copper particles. The moisture content of the obtained hydrous copper particles is shown in Table 1.
[0086] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles charged, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain each copper particle. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.
[0087] [Comparative Example 1] Hydrated copper particles were obtained in the same manner as in Example 1. The moisture content of the obtained hydrous copper particles is shown in Table 1.
[0088] <Step of drying the hydrous copper particles> 150 g of the hydrous copper particles were dried under reduced pressure conditions at a drying temperature of 50° C. for a drying time of 720 min using a shelf dryer (manufactured by Yamato Scientific Co., Ltd., constant temperature shelf dryer DX602) to obtain copper particles. In Comparative Example 1, the copper particles were dried without vibration. The amount of the obtained copper particles was 108 g. The proportion of the lump copper particles was 100 mass %.
[0089] <Crushing process> The lump copper particles were crushed in a mortar to obtain powdered copper particles.
[0090] [Comparative Example 2] Copper particles were obtained in the same manner as in Comparative Example 1, except that the reducing agent aqueous solution was not added in the step of removing the dispersant. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.
[0091] [Comparative Example 3] The copper particles were surface-treated in the same manner as in Example 1 to obtain a copper particle dispersion liquid (a).
[0092] <Step (C) of obtaining hydrous copper particles by performing solid-liquid separation of the copper particle dispersion liquid (a)> The surface-treated copper particle dispersion (a) was manually decanted to separate the solid and liquid, thereby obtaining hydrated copper particles. The moisture content of the obtained hydrated copper particles is shown in Table 1.
[0093] <Step (A) of drying the hydrous copper particles while vibrating> The hydrous copper particles were dried while vibrating in the same manner as in Example 1, except that the amount of hydrous copper particles, the drying temperature and the drying time were set to the conditions shown in Table 1, to obtain copper particles. The amount of copper particles obtained, the proportion of powdery copper particles in the obtained copper particles, and the proportion of lump copper particles are shown in Table 1.
[0094] [measurement] The following measurements were carried out in each of the Examples and Comparative Examples. Here, the copper particles obtained were in the form of powdered copper particles and lump-shaped copper particles, and various measurements were carried out on the powdered copper particles.
[0095] <Particle size (H2O)> 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering particle size measuring device (manufactured by Horiba, Ltd., product name: LA-960V2). The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H2O), D 50 Particle size (H2O), and D 95 The particle size (H2O) values were obtained respectively. Here, polyoxyethylene (20) sorbitan monolaurate was used as the dispersant.
[0096] <Particle size (img)> The copper particles were magnified and observed (10K magnification) using a scanning electron microscope to obtain images obtained by scanning electron microscopy (SEM images). The SEM images were analyzed using the image processing software ImageJ to obtain the following: 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values were obtained respectively. Specifically, the particle size was calculated according to the following procedure. 1. SEM images were imported into the image processing software ImageJ. 2. The scale of the SEM image was set as Known Distance using Set Scale. 3. The contrast threshold was adjusted using Threshold, and the image was binarized. 4. After binarization, particles were separated from the image using the Watershed method. 5. The particle size was calculated using the Analyze Particles function. The number of copper particles used to calculate the particle size was set to 200 or more. 6. From the obtained values, calculate the volume-based particle size distribution using the Area value, and D 10 Particle size (img), D 50 Particle size (img) and D 90 The particle size (img) values were obtained respectively.
[0097] Based on the particle size values obtained by the above measurement method, D 95 Particle diameter (H2O) is D 10 Divided by particle diameter (H2O), D 95 Particle size (H2O) to D 10 The value obtained by subtracting the particle size (H2O), and D 50 Particle diameter (H2O) is D 50 The values were calculated by dividing the values by the particle size (img).
[0098] <Oxygen content> The oxygen content was calculated using a nitrogen / oxygen analyzer (manufactured by LECO, product name: ON836) in accordance with JIS H1067:2002.
[0099] <Carbon content> 0.5 g of copper particles were weighed out, and 1.5 g of tungsten powder, 0.5 g of iron powder, and 0.5 g of tin powder were added as combustion improvers. The carbon content was calculated using a carbon / sulfur analyzer (manufactured by Horiba, Ltd., product name: EMIA-820W) under the following conditions: in an oxygen stream, flow rate: 3 L / min, combustion method: high-frequency heating, combustion time: 60 sec, detection method: infrared absorption method.
[0100] <Temperature for shrinkage rate of 1.0%> 1 g of copper particles was weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the copper particles were press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding were crushed to obtain a granule sample. 0.67 g of the granule sample was weighed out and filled into a cylindrical mold having a diameter of 5 mm, and the granule sample was press-molded using a hydraulic press (discharge pressure of 10 MPa), to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer (manufactured by NETZSCH, product name: TMA4000SA), measurements were performed under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000°C, and heating rate: 5°C / min, and the temperature at which the shrinkage rate was 1.0% was calculated.
[0101] <Tap density> The tap density was measured in accordance with JIS Z2512:2012.
[0102] The results of each measurement are shown in Table 1. 95 Particle diameter (H2O) is D 10 "Particle diameter (H2O) divided by" is "D 95 (H) / D 10 (H)," "D 95 Particle size (H2O) to D 10 The value obtained by subtracting the particle size (H2O) is "D 95 (H)-D 10 (H)" and "D 50 Particle diameter (H2O) is D 50 The value divided by the particle size (img) is "D 50 (H) / D 50In Table 1, "-" means that the measurement was not performed.
[0103] [Table 1]
[0104] From Table 1, the tap density of the copper particles obtained by the manufacturing method of the example is D 50 It can be seen that the tap density is improved compared to the copper particles obtained by the comparative example having the same particle diameter (img) value. In other words, it can be seen that the copper particle manufacturing method of the present embodiment can produce copper particles with improved packing properties.
[0105] From Table 1, it can be seen that the copper particle manufacturing method of the example improves the proportion of powdery copper particles in the obtained copper particles compared to the copper particle manufacturing methods of Comparative Examples 1 and 2. In other words, it can be seen that the copper particle manufacturing method of the present embodiment can further improve the proportion of powdery copper particles in the obtained copper particles.
Claims
1. The method includes a step (A) of drying the hydrous copper particles while vibrating the particles, The method for producing copper particles, wherein the moisture content of the hydrous copper particles is 30% by mass or less when the whole of the hydrous copper particles is taken as 100% by mass.
2. The method for producing copper particles according to claim 1 , wherein the moisture content of the hydrous copper particles is 5% by mass or more when the entire hydrous copper particles are taken as 100% by mass.
3. The method for producing copper particles according to claim 1 or 2, wherein in the step (A), the hydrous copper particles are dried using a vibration dryer.
4. The method for producing copper particles according to claim 1 or 2, wherein in step (A), the drying temperature is 30° C. or higher and 100° C. or lower.
5. The method for producing copper particles according to claim 1 or 2, wherein in step (A), the drying time is 10 minutes or more and 24 hours or less.
6. A step (B) of preparing a copper particle dispersion liquid (a); The method for producing copper particles according to claim 1 or 2, further comprising a step (C) of subjecting the copper particle dispersion liquid (a) to solid-liquid separation to obtain the hydrous copper particles.
7. The method for producing copper particles according to claim 6, wherein in the step (C), the hydrated copper particles are obtained by at least one method selected from a centrifugation method and a filtration method.
8. The step (B) includes a step (B-1) of dispersing a divalent copper compound in a solvent in the presence of a dispersant; The method for producing copper particles according to claim 6, further comprising a step (B-2) of reducing the divalent copper compound to obtain a copper particle dispersion liquid (a).
9. The method for producing copper particles described in claim 8, wherein in the step (B-1), the dispersant comprises at least one selected from the group consisting of gelatin, casein, sodium caseinate, ammonium caseinate, starch, dextrin, agar, sodium alginate, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, sodium polyacrylate, ammonium polyacrylate, stearic acid, polyethylene glycol, citric acid, aniline, and aniline derivatives.
10. The method for producing copper particles according to claim 1 or 2, wherein the temperature at which the copper particles have a shrinkage rate of 1.0% calculated by the following shrinkage rate measurement is 200°C or higher. [Shrinkage ratio measurement] 1 g of copper particles is weighed out, filled into a cylindrical mold having a diameter of 5 mm, and the copper particles are press-molded using a hydraulic press (discharge pressure of 10 MPa). The pellets obtained by press molding are crushed to obtain a granule sample. 0.67 g of the granule sample is weighed out, filled into a cylindrical mold having a diameter of 5 mm, and press-molded using a hydraulic press (discharge pressure of 10 MPa) to obtain a cylindrical pellet having a diameter of 5 mm and a height of 5 mm as a measurement sample. Using a thermomechanical analyzer, measurements are taken under the conditions of Ar flow rate: 200 mL / min, measurement load: 10 mN, measurement temperature range: 23 to 1000° C., and temperature rise rate: 5° C. / min, and the temperature at which the shrinkage rate reaches 1.0% is calculated.
11. The copper particles have a tap density of 2.5 g / cm as measured in accordance with JIS Z2512:2012. 3 The method for producing copper particles according to claim 1 or 2, wherein
12. The copper particles are measured by the following particle size measurement 1. 50 Particle size (H 2 The method for producing copper particles according to claim 1 or 2, wherein the diameter of the copper particles is 0.10 μm or more and 1.00 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass aqueous dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering type particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H 2 O), D 50 Particle size (H 2 O), and D 95 Particle size (H 2 O) values are obtained respectively.
13. The copper particles are measured by the following particle size measurement 1. 10 Particle size (H 2 The method for producing copper particles according to claim 1 or 2, wherein the diameter of the copper particles is 0.05 μm or more and 0.50 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass aqueous dispersant solution, and the mixture was irradiated with ultrasonic waves for 5 minutes using a laser diffraction / scattering type particle size measuring device. The volume-based particle size distribution of the copper particles was then measured. 10 Particle size (H 2 O), D 50 Particle size (H 2 O), and D 95 Particle size (H 2 O) values are obtained respectively.
14. The copper particles are measured by the following particle size measurement 1. 95 Particle size (H 2 The method for producing copper particles according to claim 1 or 2, wherein the diameter of the copper particles is 0.20 μm or more and 2.00 μm or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass aqueous solution of a dispersant, and the mixture was irradiated with ultrasonic waves in a laser diffraction / scattering type particle size measuring device for 5 minutes. Then, the volume-based particle size distribution of the copper particles was measured. 10 Particle size (H 2 O), D 50 Particle size (H 2 O), and D 95 Particle size (H 2 O) values are obtained respectively.
15. D, calculated by the following particle size measurement 1 of the copper particles 95 Particle size (H 2 O) to D 10 Particle size (H 2 The method for producing copper particles according to claim 1 or 2, wherein the value obtained by dividing the total mass of copper by the mass of the copper particles by the mass of the copper particles is 4.20 or less. [Particle size measurement 1] 0.1 g of copper particles was mixed with 1 mL of a 0.1% by mass aqueous solution of a dispersant, and the mixture was irradiated with ultrasonic waves in a laser diffraction / scattering type particle size measuring device for 5 minutes. Then, the volume-based particle size distribution of the copper particles was measured. 10 Particle size (H 2 O), D 50 Particle size (H 2 O), and D 95 Particle size (H 2 O) values are obtained respectively.
16. The method for producing copper particles according to claim 1 or 2, wherein the oxygen content of the copper particles measured in accordance with JIS H1067:2002 is 0.70 mass% or less.
17. The method for producing copper particles according to claim 1 or 2, wherein the carbon content of the copper particles calculated by the following carbon content measurement is 1.50 mass% or less. [Carbon content measurement] 0.5 g of copper particles is weighed out, and 1.5 g of tungsten powder, 0.5 g of iron powder, and 0.5 g of tin powder are added as combustion improvers. Measurement is then performed using a carbon / sulfur analyzer under the following conditions: in an oxygen stream, flow rate: 3 L / min, combustion method: high-frequency heating, combustion time: 60 sec, detection method: infrared absorption method, and the carbon content is calculated.
18. A conductive paste comprising copper particles obtained by the method for producing copper particles according to claim 1 or 2.
19. A substrate comprising the conductive paste according to claim 18 or a sintered body of the conductive paste.
20. 20. The substrate of claim 19 which is a low-temperature co-fired ceramic substrate.
Citation Information
Patent Citations
Easily crushable copper powder and method for producing the same
JP2020050947A